PERAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KESEJAHTERAAN SPIRITUAL LANSIA DI PONDOK PANTI LANSIA AT-TAQWA LAMONGAN - Novia Shinta kamaliyah; Mita Rusady; Anni Fatimatus Sholikhah; Dzurrotul Aini; Asnifatul Muadlomah; Dwi Firnanda; Ilham Dwi Sugiarto; Muhammad Asrori (JURNAL ILMIAH RESEARCH STUDENT, 2025)
Islamic religious education plays a crucial role in enhancing the spiritual well-being of the elderly at the At-Taqwa Elderly Care Home in Lamongan. With the increasing elderly population in Indonesia, spiritual support through religious education has become increasingly relevant. This study employs a qualitative approach with a case study design, collecting data through in-depth interviews with the home's administrators and direct observations. The findings indicate that activities such as congregational prayers, Quranic learning, study circles, and social religious activities effectively strengthen faith, provide meaning in life, and improve the mental and emotional health of the elderly. Thus, Islamic religious education in elderly care homes not only fulfills spiritual needs but also contributes to holistic well-being, helping the elderly live more peacefully and happily in their daily lives.